Is two better than one? Maximising follow-up of self-reported outcome measures for a stroke survivor population: Results from a study within a trial in the LoTS2Care feasibility study. Issue 4 (September 2022) - Moreau, Lauren; Holloway, Ivana; Ozer, Seline; Forster, Anne; Hulme, Claire; Hartley, Suzanne; Farrin, Amanda
Background: Improving outcome data collection rates is an essential part of managing clinical trials and ensures statistical power and generalisability of results are maintained. Studies within a trial (SWATs) provide a robust methodology to investigate the most efficient methods to maximise outcome follow-up. Methods: LoTS2Care, a feasibility cluster Randomised Controlled Trial, recruited 269 stroke survivors across 10 services, and incorporated a SWAT to evaluate the effect of questionnaire booklet format (one booklet or two) on follow-up rates for self-reported postal outcomes at 6 and 9 months post-recruitment. Available participants were individually randomised (1 : 1) by the Clinical Trials Research Unit and follow-up rates in the two groups were compared. Results: At 6 months post-recruitment, 254 participants were randomised: 126 to receive (125 posted) the single booklet; 128 to receive two booklets. By 9 months post-recruitment, 116 and 123 participants were still available in each group, respectively. For participants randomised to two booklets, return of at least one of the booklets was considered as 'followed-up'. At 6 months, 114/125 (91.2%) participants sent the single booklet returned it, compared to 108/128 (84.4%) sent two (odds ratio (OR) 1.92, 95% confidence interval (CI) 0.88 to 4.19). By 9 months, 108/116 (93.1%) participants returned the single booklet, compared to 105/123 (85.4%) sent two (OR 2.31, 95% CI 0.97 to 5.55). Conclusions: The SWAT was an inexpensive, straightforward way to test how booklet format affected follow-up rates. Larger participant numbers would be required for conclusive results. These initial findings, however, suggest that including all outcome measures in a single booklet may maximise return rates, especially in trials with similar populations, such as those living with brain injury, cognitive or speech impairment or older people.